PENGARUH POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN KARAKTER ANAK DI ERA GLOBALISASI - Wira Fimansyah (LP4MK STKIP PGRI Lubuklinggau, 2019)
The globalization era has taken place in every part of life even in the point of view and the mindset of parenting. In fact, parents are the main and most important educator. Thus, why the family is known as the first madrasah for children because the education from parents is the basis of character development and the future life of children. Through this literature study, it is expected could provide the knowledge and understanding to the parents about the family as the first madrasah and the importance of applying the right parenting for their children. This information is very useful for all parents, prospective parents, and especially for the rural communities who are considered less of knowledge about it. The method used is the literature review method to provide the knowledge and understanding of various types of parenting to build up the children's character in the globalization era by exploring the results of several types of research, journals, and books. The parenting style has a significant effect in developing the children character to be good or bad, whether they will grow into an extrovert, introvert, or ambitious person in their daily life. Therefore, parenting plays an important role in building the children's character. Considering the tight relationship between parenting and the children's character, so applying the right parenting will help parents build their child's character up. The most recomended parenting is democratic parenting.